Pregnancy: a therapeutic dilemma - Brzezińska-Wcisło, Ligia; Zbiciak-Nylec, Martyna; Wcisło-Dziadecka, Dominika; Salwowska, Natalia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Treatment during pregnancy is problematic. The Food and Drug Administration established drug categories to help in the treatment process. First-generation antihistamines are considered safe but they have sedative properties. Second-generation antihistamines cause less adverse reactions but besides cetirizine and loratadine they belong to category C. All retinoids should be avoided during pregnancy due to the risk of fetal malformations. Antimalarial drugs should be considered based on the clinical data. Sulfones can be considered as safe for use during pregnancy only with proper monitoring. Prednisone is administered in pregnancy. Other glucocorticosteroids have a different safety profile. Cyclosporine A treatment should be reserved as rescue therapy in severe stages of the disease. Treatment during pregnancy should be precise when it comes to pregnant woman and safe for the fetus.